Higher Order Thinking Skill Instrument for Science Subject in Sixth Grade of Elementary School - Putra, I Gede Adi Suwarma; Riastini, Putu Nanci; Jayanta, I Nyoman Laba (Jurnal Pedagogi dan Pembelajaran, 2024)
The lack of development of test questions that contain HOTS elements in training students to be able to think at a high-level causes students' higher order thinking skills to be low. So that the demands of the curriculum cannot be achieved optimally. This study aims to analyze the feasibility of HOTS ability instruments for grade VI elementary school students in science subjects to measure students' higher order thinking skills. This research is development research that uses the 4D model. The 4D research model consists of four stages, namely define, design, develop, and disseminate. The subject of this research is HOTS instrument. The object of this research is the quality of the items produced. The data collection techniques used in this research are quantitative observation, interviews, questionnaires, and tests. In order to test its feasibility, the multiple-choice test instrument was analyzed which included content validity test, item validity test, reliability test, differentiation test, and difficulty test. HOTS-based instruments for grade VI elementary school students in science subjects, get the results of data analysis, namely, the content validity test of the instrument is declared valid, the validity test of the instrument items is declared valid, the reliability test is declared to have high reliability, the average result of the test of differential power is included in the good criteria, and the test of the level of difficulty is included in the medium criteria. From the tests that have been carried out, the HOTS ability instrument for grade VI elementary school students in science subjects is suitable for measuring students' higher order thinking skills.